Cytoskeleton disruption by the metabolic inhibitor 3-bromopyruvate: implications in cancer therapy - Azevedo-Silva, J. (2022)
The small molecule 3-bromopyruvate (3BP), is an anticancer molecule that acts by hindering glycolysis and mitochondrial function leading to energy depletion and consequently, to cell death. In this work we have focused on understanding how the glycolytic inhibition affects cancer cell structural features. We showed that 3BP leads to a drastic decrease in the levels of beta-actin and alpha-tubulin followed by disorganization and shrinkage of the cytoskeleton in breast cancer cells. 3BP inhibits cell migration and colony formation independently of the activity of metalloproteinases. To disclose if these structural alterations occurred prior to 3BP toxic effect, non-toxic concentrations of 3BP were used and we could observe that 3BP was able to inhibit energy production and induce loss of beta-actin and alpha-tubulin proteins. This was accompanied with alterations in cytoskeleton organization and an increase in E-cadherin levels which may indicate a decrease in cancer cells aggressiveness. In this study we demonstrate that 3BP glycolytic inhibition of breast cancer cells is accompanied by cytoskeleton disruption and consequently loss of migration ability, suggesting that 3BP can potentially be explored for metastatic breast cancer therapy.